Omalizumab modulates bronchial reticular basement membrane thickness and eosinophil infiltration in severe persistent allergic asthma patients - Riccio, A M; Dal Negro, R W; Micheletto, C; De Ferrari, L; Folli, C; Chiappori, A; Canonica, G W (International journal of immunopathology and pharmacology, 2012)
Severe persistent asthma causes a substantial morbidity and mortality burden and is frequently not well controlled, despite intensive guideline-based therapy. The unique monoclonal antibody approved for patients with severe allergic asthma is omalizumab: a recombinant humanised murine against IgE antibodies. The aim of the present study is to investigate the effect of long-term anti-IgE on the thickening of the reticular basement membrane (RBM) and eosinophil infiltration in bronchial biopsies from patients with severe persistent allergic asthma. Biopsies were obtained from 11 patients with severe persistent allergic asthma before and after (12 months) treatment with omalizumab. RBM thickness and eosinophils were measured by using light microscope image analysis. A significant mean reduction in RBM thickness and eosinophil infiltration were measured after one-year omalizumab treatment. No correlation between eosinophil reduction and RBM thickness reduction was found. No correlation between each of the previous two parameters and clinical parameters was detected. In conclusion, our study showed that a substantial proportion of severe asthmatics reduced the original bronchial RBM thickness and eosinophil infiltration after one-year treatment with anti-IgE, thus emphasizing the possible role of omalizumab in affecting airway remodeling in severe persistent allergic asthma.